Kontradiksi Desentralisasi Fiskal dalam Penganggaran Pilkada 2024 di Sumatera Barat - Jumiati (KIPS - Jurnal Kajian Islam Politik dan Sosial, 2026)
This study examines the contradictions of fiscal decentralization in financing the 2024 Regional Head Election (Pilkada) in West Sumatra. Since the enactment of Law No. 10/2016, Pilkada funding has been charged to the Regional Revenue and Expenditure Budget (APBD) through a grant mechanism from local governments to election management bodies. In practice, however, this scheme generates several problems, such as delays in signing the Regional Grant Agreement (NPHD), budget politicization by both executives and legislatures, and the potential for political corruption. In fact, most Pilkada funds originate from the General Allocation Fund (DAU) transferred by the central government. This research employs a qualitative method with a literature study approach to analyze the dynamics of fiscal policy and political budgeting. The findings reveal that financing Pilkada through APBD creates inefficiency, overlapping authority, and widens the space for local political bargaining. Therefore, this study recommends shifting Pilkada financing directly to the State Revenue and Expenditure Budget (APBN) to enhance transparency, accountability, and fiscal efficiency.